SFRP2 augments WNT16B signaling to promote therapeutic resistance in the damaged tumor microenvironment - Sun, Y; Zhu, D; Chen, F; Qian, M; Wei, H; Chen, W; Xu, J (Oncogene, 2016)
Most tumors initially respond to cytotoxic treatments, but acquired resistance often follows. The tumor microenvironment (TME) is a major barrier to clinical success by compromising therapeutic efficacy, and pathological relevance of multiple soluble factors released by a therapeutically remodeled TME remains largely unexplored. Here we show that the secreted frizzled-related protein 2 (SFRP2), a Wnt pathway modulator, is produced by human primary fibroblasts after genotoxic treatments. SFRP2 induction is remarkable in tumor stroma, with transcription mainly modulated by the nuclear factor-κB (NF-κB) complex, a property shared by several effectors of the DNA damage secretory program. Instead of directly altering canonical Wnt signaling, SFRP2 augments β-catenin activities initiated by WNT16B, another soluble factor from DNA-damaged stroma. WNT16B recognizes cancer cell surface receptors including frizzled (FZD) 3/4/6, a process enhanced by SFRP2, coordinated by the co-receptor LRP6 but subject to abrogation by DKK1. Importantly, we found WNT16B plays a central role in promoting advanced malignancies particularly acquired resistance by counteracting cell death, an effect that can be minimized by a neutralizing antibody co-administered with classical chemotherapy. Furthermore, DNA damage-triggered expression of WNT16B is systemic, imaged by significant induction among diverse solid organs and circulation in peripheral blood, thereby holding promise as not only a TME-derived anticancer target but also a novel biomarker for clinical evaluation of treatment efficacy. Overall, our study substantiates the biological complexity and pathological implication of a therapy-activated TME, and provides the proof of principle of co-targeting tumor and the TME to prevent acquired resistance, with the aim of improving intervention outcome in an era of precision medicine.